HAWKING TEMPERATURE NEAR LYRA BLACK HOLE’S HORIZONS (Journal of Sciences & Technology, 2017)
A model of the Lyra universe is presented. Using the tunneling effect approach, the Hawking radiation temperature near the black hole horizon is calculated.